Numerical simulation of two-phase flow regime in horizontal pipeline and its validation - Ban, S. (Emerald Group Publishing Ltd., 2018)
Purpose: The purpose of this paper is to investigate oil-gas slug formation in horizontal straight pipe and its associated pressure gradient, slug liquid holdup and slug frequency. Design/methodology/approach: The abrupt change in gas/liquid velocities, which causes transition of flow patterns, was analyzed using incompressible volume of fluid method to capture the dynamic gas-liquid interface. The validity of present model and its methodology was validated using Bakerâs flow regime chart for 3.15 inches diameter horizontal pipe and with existing experimental data to ensure its correctness. Findings: The present paper proposes simplified correlations for liquid holdup and slug frequency by comparison with numerous existing models. The paper also identified correlations that can be used in operational oil and gas industry and several outlier models that may not be applicable. Research limitations/implications: The correlation may be limited to the range of material properties used in this paper. Practical implications: Numerically derived liquid holdup and holdup frequency agreed reasonably with the experimentally derived correlations. Social implications: The models could be used to design pipeline and piping systems for oil and gas production. Originality/value: The paper simulated all the seven flow regimes with superior results compared to existing methodology. New correlations derived numerically are compared to published experimental correlations to understand the difference between models. Â© 2018, Emerald Publishing Limited.